2004
DOI: 10.1074/jbc.m402399200
|View full text |Cite
|
Sign up to set email alerts
|

De-epoxidation of Violaxanthin in Light-harvesting Complex I Proteins

Abstract: The conversion of violaxanthin (Vx) to zeaxanthin (Zx) in the de-epoxidation reaction of the xanthophyll cycle plays an important role in the protection of chloroplasts against photooxidative damage. Vx is bound to the antenna proteins of both photosystems. In photosystem II, the formation of Zx is essential for the pH-dependent dissipation of excess light energy as heat. The function of Zx in photosystem I is still unclear. In this work we investigated the de-epoxidation characteristics of light-harvesting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 52 publications
5
42
1
Order By: Relevance
“…To find out whether this is also true for Lhca5, we compared the pigment stoichiometry of r-Lhca5 with those published for r-Lhca1-r-Lhca4 (21). From Table I it is obvious that r-Lhca5 binds pigments in a unique stoichiometry, although there are similarities to other r-Lhcs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To find out whether this is also true for Lhca5, we compared the pigment stoichiometry of r-Lhca5 with those published for r-Lhca1-r-Lhca4 (21). From Table I it is obvious that r-Lhca5 binds pigments in a unique stoichiometry, although there are similarities to other r-Lhcs.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant Lhca2 and Lhca4 bind only two carotenoids per monomer (5,7,19,21), in contrast to three in Lhca3 (19,21,24). Whether Lhca1 binds two or three carotenoids is still under debate (5,15,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…high-light) there is a differential expression of LHCI genes (Bailey et al, 2001;Ensminger et al, 2004;Gáspár et al, 2006). On the other hand, Wehner et al (2004) suggested that the zeaxanthin formed in LHCI proteins is involved in an antioxidative mechanism implicated in suppression of ROS-triggered lipid peroxidation rather than heat energy dissipation (NPQ), which could be consistent with our observations on the accumulation of zeaxanthin ( Figure 3B) which can function as antioxidant, as evidenced by the amount of peroxidized lipids (Figure 4) and the invariable value of NPQ ( Figure 2C). …”
Section: Expression Of Psbs Andmentioning
confidence: 99%
“…On the other hand, zeaxanthin also appears to have a role in tolerance to photo-oxidative stress protecting membranes against lipid peroxidation by a different mechanism from NPQ (Lichtenthaler and Schnidler, 1992). Carotenoids are essential components of light-harvesting chlorophyll (chl) a/b binding (LHC) protein (Wehner et al, 2004) and therefore the chemical transformation of the xanthophyll cycle induces a reorganization in light-harvesting complex (LHC) proteins (i.e. from a state of efficient light harvesting to a state of high thermal energy dissipation; Nelson and Yocum, 2006).…”
mentioning
confidence: 99%